Flood Analysis with HEC-RAS: A Case Study of Tigris River - Selman Ogras; Fevzi Onen (Advances in Civil Engineering)
Floods are seen in countries in tropical climatic zones, both in terms of quantity and harm. The non-tropical climate countries such as Turkey are also affected by the floods. The geographical structure of Turkey is extremely complex and varies even at short distance. Therefore, the shape and effects of the floods vary from region to region. Considering the peculiar state of nature, floods, which are the greatest disasters after the earthquake, are unlikely to occur. But floods are becoming more risky for human beings day by day because of the population growth, need of water and settlements, wrong zoning plan, and unplanned engineering practices. Regulation comes at the beginning of measures to be taken to minimize the damages that occur from the floods. To do these studies, it must be specified the changes which bridges on the rivers and hydraulics structures like regulator cause in cross sections and the effects of the changes to water surface profile due to the natural state of the land. In order to determine water surface profiles, many software packages have been developed for facilitating the analysis and calculation. HEC-RAS is one of them. In this study, the floodplain analysis was handled between Diyarbakır-Silvan Highway and historical Ten-Eyed Bridge. There are three bridges, and one of which are historical bridges, as well as fertile agricultural lands, facilities, and hospitals in the Dicle University campus, the Hevsel Gardens on the UNESCO World Cultural Heritage List, and some residential areas on the route under study. The aim of the study we have done in this much important route is to evaluate the flood areas and create a flood hazard map which can predict risky areas. And also contributing to the Tigris River Rehabilitation Project is one of the aims. About methodology, the 1/1000 maps of the study area were digitized using the AutoCAD Civil 3D program and cross sections were made by obtaining the digital elevation models of the region. The obtained cross sections were defined in the HEC-RAS software, and the hydraulic characteristics of the flood bed and the water surface profiles of the Q25, Q50, Q100, and Q500 flood recurring and one-dimensional floodplain analysis of the Tigris River were determined.